RTEMS Core Analysis for Space Applications - Nicodemos, Fernando; Saotome, Osamu; Lima, George (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Overheads due to context switching and external interrupt management are core characteristics for Real-Time Operating Systems (RTOS) since they play a central role in their performance and timeliness. In this paper we evaluate two core characteristics for the Real-Time Executive for Multiprocessor Systems (RTEMS), an operating system used for supporting space applications. Our assessment makes use of an external non-intrusive measurement tool based on a Field-Programmable Gate Array (FPGA). Measurement data are then transferred to an external computer and analyzed off-line. Experiments are carried out on a device that complies with the Brazilian space program recommendation.